Identifying and Managing Pain in People with Alzheimer’s Disease and Other Types of Dementia: A Systematic Review - Husebo, Bettina S. (CNS Drugs, 2016)
BACKGROUND AND OBJECTIVE: Pain in patients with Alzheimer’s disease is a complex issue; these patients suffer from the common causes of acute and chronic pain, and some also have neuropathic or nociceptive pain. Whatever the mechanism of pain in these patients, their pain will require careful assessment and management, to insure the correct type and level of analgesia is given. The objective of this systematic review was the identification of studies that have investigated the efficacy of different analgesics on pain intensity or pain-related behavior during nursing home stay and at the end of life. METHODS: A search using pain, pain treatment, and dementia MESH terms and keywords was conducted (October 15, 2015) in MEDLINE, EMBASE, PsychINFO, CINAHL, and Cochrane libraries. RESULTS: Our search yielded 3138 unique hits, published between 1990 and October 2015. We read titles and abstracts, identified 124 papers for full-text evaluation, and included 12 papers to reflect and synthesize the following questions: (1) Which pain assessment tools for people with dementia are responsive to change in pain intensity scores? (2) Which analgesics are efficacy-tested by controlled trials including people with dementia living in nursing homes, including at the end of life? (3) Which outcome measures have been used to identify pain, pain behavior, and/or treatment efficacy in people with dementia? CONCLUSION: Despite increased use of analgesics, pain is still prevalent in people with dementia. Validated pain tools are available but not implemented and not fully tested on responsiveness to treatment. Official guidelines for pain assessment and treatment addressing people with dementia living in a nursing home are lacking. The efficacy of analgesic drug use on pain or neuropsychiatric behavior related to dementia has been hardly investigated. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40263-016-0342-7) contains supplementary material, which is available to authorized users.